Morphometric variation among the populations of planktonic shrimp, Acetes japonicus in the west coast of Peninsular Malaysia - Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Wan Nurul Izzah,; Aziz, D.; Ara, Roushon (Academic Journals, 2013)
Planktonic shrimp Acetes japonicus is found in the west of Peninsular Malaysia around the year. The study was conducted to observe the morphometric variation among the population of Acetes japonicus from four different sites along the coastal waters of Malacca, Penang and Perlis. Morphometric data of this species was analyzed using ANOVA and PRIMER software to investigate the degree of similarity among the populations of A. japonicus collected from four different sites (Malacca, Penang and two sides in Perlis) in the west coast of Peninsular Malaysia. The ANOVA showed that the mean difference of total length, standard length, carapace length and abdomen length amongst the four populations were highly significant (p<0.05). No significant difference was observed amongst the telson length of four populations (p>0.05). Dendrogram based on both sexes of morphometric characters showed three clusters amongst the populations. Sg. Berembang and Pantai Bersih populations were clustered in one group, Sg. Baharu population was in another group and both groups were well separated from the Klebang Besar population. The highest morphometric resemblance is observed between Sg. Berembang and Pantai Bersih populations which fall under the same group with a similarity of 99.67%. Analysis of variance showed that shrimp samples from the four sites differed significantly (p<0.05) based on morphometric characters.